Penerapan X Means Clustering Pada UMKM Kab Banyumas Yang Mendukung Mega Shifting Consumer Behavior Akibat Covid-19 - Rifki Adhitama; Auliya Burhanuddin; Atik Febriani (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2022)
The Covid-19 has become a epidemic that is troubling the public because of the extent and speed of the virus spreading. The Covid-19 has resulted in people being unable to move outside their homes freely so that household consumption has decreased. This condition is similar to the crisis in 1997-1998, where MSMEs and small traders could survive. In Banyumas district, the percentage of MSMEs are in the large, medium, and small groups that can support the habit of Mega Shifting, or businesses that can be done at home so that they can be an economic savior in the covid-19. Clustering is a method of grouping similar objects which are taken from several criteria. X-Means is a grouping method that can be used to effectively calculate the value of K. As for testing the quality of a cluster using the Purity test method, it is said to be